Improved growth and tuber quality of transgenic potato plants overexpressing either NHX antiporter, CLC chloride channel, or both - Ayadi, Mariem (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.